2022
DOI: 10.1186/s13223-022-00691-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lockdowns on paediatric asthma hospital presentations over three waves of COVID-19 pandemic

Abstract: Public health measures to mitigate the COVID-19 pandemic have altered health care for chronic conditions. The impact of the COVID-19 pandemic on paediatric asthma, the most common chronic respiratory cause of childhood hospitalisation, in Australia, remains unknown. In a multicentre study, we examined the impact of three waves of COVID-19 on paediatric asthma in New South Wales Australia. Time series analysis was performed to determine trends in asthma hospital presentations in children aged 2–17 years before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…During autumn 2020, when many COVID-19 restrictions in Brussels were still in place [22,23], no decrease in the number of wheezing episodes (as compared to 2019) was observed despite a reduction in overall outpatient attendance. This nding contrasts with other studies that all documented a decrease in wheezing episodes with the onset of the COVID-19 pandemic and its lockdown measures in 2020 [24][25][26][27]. However, most of the studies report on the annual incidence [25,26] or incidence during strict lockdown periods [24,27] which makes comparison di cult.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…During autumn 2020, when many COVID-19 restrictions in Brussels were still in place [22,23], no decrease in the number of wheezing episodes (as compared to 2019) was observed despite a reduction in overall outpatient attendance. This nding contrasts with other studies that all documented a decrease in wheezing episodes with the onset of the COVID-19 pandemic and its lockdown measures in 2020 [24][25][26][27]. However, most of the studies report on the annual incidence [25,26] or incidence during strict lockdown periods [24,27] which makes comparison di cult.…”
Section: Discussionmentioning
confidence: 71%
“…This nding contrasts with other studies that all documented a decrease in wheezing episodes with the onset of the COVID-19 pandemic and its lockdown measures in 2020 [24][25][26][27]. However, most of the studies report on the annual incidence [25,26] or incidence during strict lockdown periods [24,27] which makes comparison di cult.…”
Section: Discussionmentioning
confidence: 71%
“…Previous study from our group also found a significant reduction of 50–70% in asthma hospital presentations during the lockdown periods in NSW. 36 In a separate meta-analysis of 35 studies, the authors found that adoption of non-pharmaceutical public health interventions was associated with a 4.68% decrease in daily cases, 4.80% decrease in daily deaths, 1.90% decrease in the COVID-19 reproduction number and 16.5% decrease in COVID-19 daily ICU admission. 37 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the advantages arising from the pandemic, such as improved air quality and increased parental supervision, may have contributed to protecting children from diseases and adverse health conditions. A number of studies around the world have discussed the decline in hospital admissions among children [ 41 – 49 ].…”
Section: Discussionmentioning
confidence: 99%